2012
DOI: 10.1021/ac301654g
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Method for Assay of Drug-Induced Apoptosis Using Fluorescence Correlation Spectroscopy

Abstract: Apoptosis plays a crucial role in many biological processes and pathogenesis of various malignancies and diseases of the immune system. In this paper, we described a novel method for sensitive detection of drug-induced apoptosis by using fluorescence correlation spectroscopy (FCS). The principle of this method is based on the assay of DNA fragmentation in the process of the drug-induced apoptosis. FCS is a single molecule method, and it can be used for sensitive and selective assay of DNA fragmentation without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Fluorescence correlation spectroscopy (FCS) is a technique for single-molecule detection that analyzes the fluctuations in fluorescence resulting from the Brownian motion of fluorescent molecules in a very small detection volume 1921 . Previous study using FCS has demonstrated DNA molecules of different sizes released from cells following drug-induced apoptosis 22 . As noted in our previous study, a maximum entropy method (MEM)-based fitting procedure to analyze FCS raw data, called MEMFCS 23 , was successfully used to investigate the size distributions of DNA molecules in the multiple-component model.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence correlation spectroscopy (FCS) is a technique for single-molecule detection that analyzes the fluctuations in fluorescence resulting from the Brownian motion of fluorescent molecules in a very small detection volume 1921 . Previous study using FCS has demonstrated DNA molecules of different sizes released from cells following drug-induced apoptosis 22 . As noted in our previous study, a maximum entropy method (MEM)-based fitting procedure to analyze FCS raw data, called MEMFCS 23 , was successfully used to investigate the size distributions of DNA molecules in the multiple-component model.…”
Section: Introductionmentioning
confidence: 99%
“… Maiti et al first applied MEM to FCS and developed the MEMFCS method . MEMFCS has been successfully applied to study the diffusion of polymer chains, Alzheimer’s disease, drug-induced apoptosis, etc. In the theoretical part of our work, a theoretical diffusion model of RLSCS was proposed by introducing the Mie scattering theory. This model is derived from FCS, but its key part has been revised due to some intrinsic characteristics of noble metal nanoparticles.…”
mentioning
confidence: 99%
“…34 So far, FCS has been used in immunoassays, 35 drug screening, 36 and detection of drug-induced cell apoptosis. 37 In this paper, we reported a homogeneous immunoassay for the sensitive detection of FB 1 in maize. In this study, a competitive immunoassay model was used, and uorescent labeled FB 1 was used as a tracer.…”
Section: Introductionmentioning
confidence: 99%